Avaliatividade em produção de textos a partir do gênero editorial - Albuquerque, Maria Eulália Tomasi; Selle, Camila Noal; Lima, Letícia Oliveira de (Linguagens & Cidadania, 2017)
This article analyses the text marks which show the student’s opinion in their text production, the linguistic resources that are available in these text productions, aiming for contribution to indicate the predominant subsystem of the Theory of Evaluation. This work is characterized as a deductive, qualitative and quantitative research, with exploratory character, and it is considered a case study. The corpus of this research is constituted by 22 text productions or, in other words, interpretations of texts produced by students of the ninth grade of the Basic Education of a school in Santa Maria, RS. After choosing the corpus, we began to analyze it and to interpret it to find the results. Most students presented their opinions based on the emotion when facing a controversial fact, with the predomination of the attitude subsystem. We didn’t expect that so many occurrences would happen in the graduation subsystem. We noticed that the Appraisal System is common mainly in texts and that the evaluations we make show not only our opinion, as they also express rules, conducts and principles considered right for some, wrong for others and vice-versa.